The European Virus Archive Goes Global: A Growing Resource for Research - Christine MA Prat; Jean-Louis Romette (Proceedings, 2020)
The European Virus Archive (EVA) was created in 2008 with funding from the FP7-EU Infrastructure Programme, in response to the need for a coordinated and readily accessible collection of viruses that could be made available to academia, public health organisations and industry. Within three years, it developed from a consortium of nine European laboratories to encompass associated partners in Africa, Russia, China, Turkey, Germany and Italy. In 2014, the H2020 Research and Innovation Framework Programme (INFRAS projects) provided support for the transformation of the EVA from a European to a global organisation (EVA-GLOBAL). The EVA now operates as a non-profit consortium, with 37 partners and associated partners from 29countries. In this communication, we outline the structure and goals of the EVA, and how the EVA has helped to respond to Viral Public Health Emergencies. Our aim is to bring to the attention of researchers the wealth of products it can provide and to illustrate how they can gain access to these resources, free of charge.